2019
DOI: 10.1371/journal.pone.0214107
|View full text |Cite
|
Sign up to set email alerts
|

Iron nanoparticle-labeled murine mesenchymal stromal cells in an osteoarthritic model persists and suggests anti-inflammatory mechanism of action

Abstract: Osteoarthritis (OA) is characterized by cartilage degradation and chronic joint inflammation. Mesenchymal stem cells (MSCs) have shown promising results in OA, but their mechanism of action is not fully understood. We hypothesize that MSCs polarize macrophages, which are strongly associated with joint inflammation to more homeostatic sub-types. We tracked ferumoxytol (Feraheme™, iron oxide nanoparticle)-labeled murine MSCs (Fe-MSCs) in murine OA joints, and quantified changes to joint inflammation and fibrosis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 38 publications
(48 reference statements)
0
23
0
Order By: Relevance
“…Hamilton et al demonstrated a decrease in proportion of iNOS and reduction of pro-inflammatory macrophages after MSCs injection in a murine OA model (78). It was reported that MSCs decreased synovial inflammation and fibrosis (78).…”
Section: Macrophages and Mesenchymal Stem Cellsmentioning
confidence: 99%
“…Hamilton et al demonstrated a decrease in proportion of iNOS and reduction of pro-inflammatory macrophages after MSCs injection in a murine OA model (78). It was reported that MSCs decreased synovial inflammation and fibrosis (78).…”
Section: Macrophages and Mesenchymal Stem Cellsmentioning
confidence: 99%
“…Finally, M2 macrophages promote the repair of damaged tissues. In the mouse OA model, Hamilton et al show that MSC treatment (intra-articular injection) down-regulates the level of iNOS in macrophages, and finally decreases the formation of M1 macrophages [ 51 ]. Collectively, the above findings suggest that MSCs suppress inflammation by converting macrophages into the M2 phenotype, which would make them a promising therapeutic reagent for OA.…”
Section: Macrophages Are An Emerging Target For Oa Treatmentmentioning
confidence: 99%
“… [ 16 ] Rapamycin Primary human monocytes Patients with osteoarthritis mTOR Enhance the function of M1 macrophages and inhibit the activity of M2 macrophages Preclinical stage/NA DXMS promotes the conversion of macrophages into M2 macrophages to relieve OA symptoms. [ 16 , 47 ] Biological molecules Cell Mesenchymal stem cell (MSC) Synovial macrophages of OA patients In vitro co-culture OA model consisting of patient-matched cartilage and macrophages NA Inhibit the activity of M1 macrophages and induce polarization of M2 macrophages Preclinical stage/NA MSCs promote the formation of M2 macrophages, thereby relieving OA symptoms [ 46 , 51 ] TissueGene-C Human joint macrophages Patients with osteoarthritis NA Promote the formation of M2 macrophages Phase III of a clinical trial/NA TissueGene-C induces the formation of M2 macrophages, thereby relieving pain in patients with OA. [ 52 , 53 ] Protein R-spondin-2 NA NA Wnt/β-catenin NA Preclinical stage/NA The formatio...…”
Section: Table A1mentioning
confidence: 99%
“…MSCs have been widely studied as a therapeutic tool for OA due to their chondrogenic potential and immunomodulatory capacities [ 117 ]. MSCs can not only suppress the activation of M1 macrophages and reprogram them to polarize into M2 macrophages, but can also ameliorate synovial inflammation in a mouse OA model [ 117 , 118 ]. However, M1 macrophages have been shown to impede the chondrogenic differentiation of MSCs, indicating that although MSCs can improve the inflammatory environment and induce M2 polarization, exacerbated inflammation can in turn inhibit their functions [ 41 ].…”
Section: Application Of Immunomodulatory Biomaterials In Musculoskeletal Soft Tissue Regenerationmentioning
confidence: 99%